An Implementation Of Government Regulation On Growth Levels And Mandatory Compliance MSME Tax - Renny Maisyarah (Sean Institute, 2024)
This research examines the implementation of government regulations related to growth rates and tax obligations for Micro, Small and Medium Enterprises (MSMEs) in Indonesia. The focus of the research is to evaluate the effectiveness of MSME tax policies regulated in Government Regulations, as well as their impact on the growth and sustainability of MSME businesses. The research method used is a qualitative approach with in-depth interview techniques and document analysis. Data is collected from various sources, including government officials, MSMEs and tax experts. Data analysis was carried out using the thematic method to identify patterns and trends in the implementation of MSME tax policies. The research results show that the implementation of MSME tax regulations has provided several benefits, such as simplifying the tax process and reducing the administrative burden for MSME players. However, the research also found several significant challenges, including a lack of understanding and socialization of tax policies among MSMEs, as well as difficulties in accessing adequate technical support and information. In addition, this research identifies that although there has been an increase in MSME tax compliance, many MSME actors still operate in the informal sector and have not been fully integrated into the formal tax system. Factors such as low financial literacy, distrust of government institutions, and negative perceptions of tax obligations are the main obstacles to implementing this policy. The conclusion of this research shows that to increase the effectiveness of MSME tax regulations, the government needs to increase tax outreach and education efforts, provide better technical support, and build stronger trust and partnerships with MSME actors. In this way, MSME taxation policies can more effectively encourage economic growth, increase state income, and support the sustainability of MSME businesses in Indonesia.